2009
DOI: 10.3122/jabfm.2009.03.080210
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Immigration on Complementary and Alternative Medicine Use in Hispanic Patients

Abstract: Results: Sixty-six percent of patients had used a CAM substance within the past year. Ninety-seven percent of the patients were immigrants (primarily from Mexico, El Salvador, and Guatemala). Differences in CAM use between recently arrived (<9 years) and long-term immigrants (>10 years) were not significant. Ninetyfour percent of patients using CAM reported using herbal/tea/plant-based substances, with the most frequent reason for CAM use being digestive problems. Although most CAM substances were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…The selective migration perspective (or ‘healthy migrant hypothesis’) posits that immigrants are healthier than non-migrants in their origin countries and may be healthier than U.S. natives [3638], and therefore do not need formal health services, even routine ones. In addition, immigrants may rely on other forms of health promotion such as traditional healing practices, e.g., acupuncture, or familial and communal social support [3942]. Both of these explanations hinge on the idea that immigrants understand their health status and the role of formal healthcare differently than the U.S. born, since most originate from countries with distinct (or limited) healthcare systems and beliefs about what constitutes a healthy and happy life [43].…”
Section: Discussionmentioning
confidence: 99%
“…The selective migration perspective (or ‘healthy migrant hypothesis’) posits that immigrants are healthier than non-migrants in their origin countries and may be healthier than U.S. natives [3638], and therefore do not need formal health services, even routine ones. In addition, immigrants may rely on other forms of health promotion such as traditional healing practices, e.g., acupuncture, or familial and communal social support [3942]. Both of these explanations hinge on the idea that immigrants understand their health status and the role of formal healthcare differently than the U.S. born, since most originate from countries with distinct (or limited) healthcare systems and beliefs about what constitutes a healthy and happy life [43].…”
Section: Discussionmentioning
confidence: 99%
“…30 While our population was primarily concerned about weight loss, justification for CAM use is diverse. For example, 2 separate studies conducted in Los Angeles, California, showed that digestive problems 17 and pain 9 were the most common reasons for CAM usage. In addition, a study of a Hispanic community in South Carolina reported infection as the main reason for CAM use.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to other Hispanic groups [35][36][37], the specific methods, usage frequency, and conditions under which CAM methods are employed appears by MSFW group and illness [10,13,35,38,39]. It has been reported that older foreign-born immigrants appear to preferentially use CAM [35] but it is uncertain whether this is also the case for aging MSFW.…”
mentioning
confidence: 95%